Fe-deficiency-induced chlorosis 1 is essential for chloroplast iron transport and homeostasis under continuous light conditions in Arabidopsis - Jumei Zhang; Lei You; Hai Liu; Sheng Luo; Ruiying Li; Shaowu Xue; Xuelei Lai; Honghong Hu (Cell Reports)
Summary: Chloroplasts require iron for photosynthesis; however, the transport mechanisms remain poorly understood. This study identifies Arabidopsis Fe-deficiency-induced chlorosis 1 (FIC1), localized in the chloroplast inner membrane, as essential for iron redistribution from developed to newly developing leaves under continuous light (CL) conditions. CL induces FIC1 expression in newly developing leaves. fic1 displays chlorosis in newly developing leaves under iron deficiency or CL, with reduced levels of iron and photosynthetic complexes, along with an overaccumulation of reactive oxygen species (ROS). Iron supplementation alleviates these phenotypes. FIC1 functionally complements iron transport defects in fet3fet4 yeast and enhances iron uptake in Xenopus oocytes. Expressing PIC1 (PERMEASE IN CHLOROPLAST 1) under FIC1 promoter rescues both the deficits in iron/chlorophyll content and ROS accumulation in fic1. Furthermore, FIC1 modulates iron homeostasis-related gene expression under CL. These findings establish FIC1 as a chloroplast iron importer that is essential for prioritizing iron allocation to young tissues during prolonged light exposure.